The NADPH oxidase a of Verticillium dahliae is essential for pathogenicity, normal development, and stress tolerance, and it interacts with yap1 to regulate redox homeostasis - Vangalis, Vasileios; Papaioannou, Ioannis A.; Markakis, Emmanouil A.; Knop, Michael; Typas, Milton A. (Journal of Fungi, 2021)
Maintenance of redox homeostasis is vital for aerobic organisms and particularly relevant to plant pathogens. A balance is required between their endogenous ROS production, which is important for their development and pathogenicity, and host-derived oxidative stress. Endogenous ROS in fungi are generated by membrane-bound NADPH oxidase (NOX) complexes and the mitochondrial respiratory chain, while transcription factor Yap1 is a major regulator of the antioxidant response. Here, we investigated the roles of NoxA and Yap1 in fundamental biological processes of the important plant pathogen Verticillium dahliae. Deletion of noxA impaired growth and morphogenesis, compromised formation of hyphopodia, diminished penetration ability and pathogenicity, increased sensitivity against antifungal agents, and dysregulated expression of antioxidant genes. On the other hand, deletion of yap1 resulted in defects in conidial and microsclerotia formation, increased sensitivity against oxidative stress, and down-regulated antioxidant genes. Localized accumulation of ROS was observed before conidial fusion and during the heterokaryon incompatibility reaction upon nonself fusion. The frequency of inviable fusions was not affected by the deletion of Yap1. Analysis of a double knockout mutant revealed an epistatic relationship between noxA and yap1. Our results collectively reveal instrumental roles of NoxA and ROS homeostasis in the biology of V. dahliae.
Gesehen am 31.01.2022